Systematic literature review on the theory of Social Embeddedness of Thriving at Work - Listya Istiningtyas; Debora E. Purba; Elizabeth K. Poerwandari; Bagus Takwin; Mirra N. Milla (SA Journal of Industrial Psychology)
Orientation: Industrial and organisational psychology has increasingly focussed on Thriving at Work (TAW), particularly shaped by the Social Embeddedness of Thriving at Work (SEMTW) model, which examines how employees’ social interactions within the workplace enhance their growth and performance.